THE ANALYSIS OF SIGN POSTS WORDS AND PHRASES ERROR IN STUDENTS’ WRITING ESSAY - Rusdin Rusdin Rusdin (Journal of English Language Teaching and Literature (JELTL), 2022)
This study was conducted to investigate and find out the student errors in using signposts in writing essays. Therefore, this study focused on finding the level of students’ ability in using signposts and the types of students’ errors in using signposts. 9 students of the fourth semester of English Education Program STKIP Dompu are taken as samples of the study. To obtain the data needed in this research the researcher tries to investigate the object by applying the descriptive quantitative method. The result of the test shows: (1) the mean score of the students in using signposts in writing paragraphs was 11, 22. It means that the students of English Education Program STKIP Dompu in applying signposts in essay writing were “very poor level”. (2) The types of students’ errors in using signposts in writing paragraphs are classified into four types: omissions errors, additions errors, misformations errors, and misordering errors.